Why Pregnancy Is Not Enough: Judicial Interpretation of “Urgent Grounds” in Child Marriage Dispensation Cases at the Madiun Religious Court - Berlina Cahya Putri, Otavia; Santoso, Lukman; Saujan, Iqbal (Elkuator Research and Publication, 2025)
This article examines how Muslim judges interpret the statutory requirement of “urgent grounds” in child marriage dispensation cases arising from pregnancies outside of wedlock at the Madiun Religious Court. Although the two cases share similar factual circumstances—pregnancies resulting from zinā (adultery) involving girls below the minimum legal marriage age—the judicial outcomes diverged significantly. The article aims to identify the factors shaping this divergence and to illuminate how state law, Islamic moral norms, and psychosocial considerations interact within religious court adjudication. Employing a socio-legal approach that combines document analysis of two judicial decisions with in-depth interviews involving three key informants, the study finds that “urgent grounds” is an elastic category heavily shaped by the interpretive discretion of Muslim judges. In the first case, a two-month pregnancy was construed as a moral and social emergency requiring immediate resolution through marriage. Conversely, the eight-month pregnancy in the second case was understood as an indicator of child vulnerability that necessitated preventing, rather than facilitating, early marriage. These findings demonstrate that the dispensation mechanism is not a mechanical application of legal rules but an interpretive arena in which judges negotiate statutory texts, Islamic legal maxims, cultural norms, and the best interests of the child. The article argues that such interpretive variation reflects the interplay among Islamic law, state law, and socio-cultural values in shaping contemporary Islamic family court judgments in Indonesia. [Artikel ini mengkaji bagaimana hakim Pengadilan Agama Madiun menafsirkan persyaratan “alasan mendesak” dalam perkara dispensasi perkawinan anak yang diajukan akibat kehamilan di luar nikah. Meskipun kedua perkara memuat kondisi faktual serupa—kehamilan akibat zina oleh anak perempuan yang belum mencapai batas usia minimal perkawinan—putusan yang dihasilkan berbeda secara signifikan. Artikel ini bertujuan menelusuri faktor-faktor yang membentuk perbedaan tersebut serta mengungkap bagaimana hukum negara, nilai moral Islam, dan pertimbangan psikososial berinteraksi dalam praktik peradilan agama. Melalui pendekatan sosio-legal yang memadukan analisis dokumen atas dua putusan dengan wawancara mendalam terhadap tiga informan kunci, penelitian ini menemukan bahwa persyaratan “alasan mendesak” merupakan kategori yang lentur dan sangat dipengaruhi oleh diskresi interpretatif para hakim. Pada kasus pertama, kehamilan dua bulan dikonstruksikan sebagai kedaruratan moral–sosial yang menuntut penyelesaian segera melalui perkawinan. Sebaliknya, pada kasus kedua, kehamilan delapan bulan dipahami sebagai indikator kerentanan yang justru memerlukan pencegahan terhadap perkawinan anak. Temuan ini menunjukkan bahwa mekanisme dispensasi nikah bukan sekadar penerapan hukum secara mekanis, melainkan arena interpretatif di mana hakim menegosiasikan teks hukum, kaidah fikih, nilai budaya, serta prinsip kepentingan terbaik bagi anak. Artikel ini berargumentasi bahwa variasi interpretasi tersebut mencerminkan keterkaitan antara hukum Islam, hukum negara, dan nilai sosio-kultural dalam membentuk putusan pengadilan keluarga Islam kontemporer di Indonesia.]